2011
DOI: 10.1007/s10877-011-9305-1
|View full text |Cite
|
Sign up to set email alerts
|

Cardioplegia and ventricular late potentials in cardiac surgical patients

Abstract: ABSTRACT. Background and objective. Ventricular late potentials (LP) recording with signal-averaged electrocardiogram allow identifying patients at risk of sudden death and ventricular tachycardia. Cardiac surgery with cardiopulmonary bypass (CPB) could predispose to the development of myocardial ischemia related to imperfect cardioplegia. To the best of our knowledge, no study investigated the protection of cardioplegia and CPB regarding the occurrence of LP in patients without previous myocardial infarction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Because VLP compared with normal ECG signal waveform has a relative independence, at the same time ICA algorithm can accurately distinguish relatively independent component from the ECG, so it can be used to identify VLP. Svensson's [6] research showed that the analysis of VLP based on single guide league was superior to analysis of vector amplitude based on orthogonal XYZ three guide leagues. The processing method of traditional single guide league is template matching [7], although this method is simple, it is influenced seriously by the form of ECG waveform and high frequency noise, therefore it is not suitable for extracting VLP due that VLP signal has a property of high frequency.…”
Section: H Liu Et Al / Journal Of Information and Computationalmentioning
confidence: 99%
“…Because VLP compared with normal ECG signal waveform has a relative independence, at the same time ICA algorithm can accurately distinguish relatively independent component from the ECG, so it can be used to identify VLP. Svensson's [6] research showed that the analysis of VLP based on single guide league was superior to analysis of vector amplitude based on orthogonal XYZ three guide leagues. The processing method of traditional single guide league is template matching [7], although this method is simple, it is influenced seriously by the form of ECG waveform and high frequency noise, therefore it is not suitable for extracting VLP due that VLP signal has a property of high frequency.…”
Section: H Liu Et Al / Journal Of Information and Computationalmentioning
confidence: 99%